2018
DOI: 10.1007/s00122-018-3104-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-QTL analysis of seed iron and zinc concentration and content in common bean (Phaseolus vulgaris L.)

Abstract: Twelve meta-QTL for seed Fe and Zn concentration and/or content were identified from 87 QTL originating from seven population grown in sixteen field trials. These meta-QTL include 2 specific to iron, 2 specific to zinc and 8 that co-localize for iron and zinc concentrations and/or content. Common bean (Phaseolus vulgaris L.) is the most important legume for human consumption worldwide and it is an important source of microelements, especially iron and zinc. Bean biofortification breeding programs develop new v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 86 publications
(107 reference statements)
3
70
0
Order By: Relevance
“…Even though different methods were used to locate genomic regions/genes for Fe and Zn concentration in mung bean, the overlapping regions indicated common genomic regions that are responsible for Fe and Zn accumulation in mung bean. Correlation between minerals was observed for mung bean by Singh R. et al (2017) and similar results observed in common bean, where the majority of QTLs for Fe and Zn accumulation were located together ( Izquierdo et al, 2018 ). An association study of Fe, Se, and Zn in the garden pea have also indicated that loci related to Fe and Zn are clustered ( Diapari et al, 2015 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Even though different methods were used to locate genomic regions/genes for Fe and Zn concentration in mung bean, the overlapping regions indicated common genomic regions that are responsible for Fe and Zn accumulation in mung bean. Correlation between minerals was observed for mung bean by Singh R. et al (2017) and similar results observed in common bean, where the majority of QTLs for Fe and Zn accumulation were located together ( Izquierdo et al, 2018 ). An association study of Fe, Se, and Zn in the garden pea have also indicated that loci related to Fe and Zn are clustered ( Diapari et al, 2015 ).…”
Section: Discussionsupporting
confidence: 77%
“…As this marker was validated as a KASP assay for mung bean it could be useful for mung bean nutritional breeding even if it was evaluated on a different genotype panel. Although there is no meta-QTL analysts in mung bean yet, a multi population comparison in common bean found YSL to be one of the gene families affecting iron and zinc uptake (Izquierdo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Iron biofortification research has primarily focused on crops that have been shown to be relatively high in iron and demonstrate a genetic diversity for Fe content [14]. For example, common beans have been shown to have diversity in Fe content, ranging from 50 to 100 µg/g [15,16], and pearl millet has shown a range of 30–80 µg/g [17]. Improvement in Fe status following prolonged consumption has been demonstrated in humans and in an animal model when the Fe concentration in the common bean or pearl millet has been compared at these extreme levels [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Pulses have a uniformly higher amount of Fe and Zn compared to the cereals and are a better source of micronutrients. Izquierdo et al ( 48 ), using a meta-QTL analysis in 7 populations, identified three major QTL regions governing seed Fe and Zn content and concentration in seeds. Many other QTLs for Fe and Zn content ( Table 1 ) have also been reported in common bean using SSR markers ( 49 , 51 ), in lentil using SNP markers ( 54 , 55 , 58 ), and in peas using SSR ( 60 ) and SNP markers ( 59 ).…”
Section: Introductionmentioning
confidence: 99%